Probing the effects of non-base-triple-forming nucleotides on triplex formation - Liu, Yiran (2017)
Triplex is emerging as a prevalent structural element found in DNA, RNA and DNA-RNA structures for diverse biological functions. Better understanding of the factors affecting nucleic acid triplex structures may help develop an accurate method for the search for novel functional triplexes present in nature, and develop highly stable artificial triplex structures for biological applications. In this thesis, we characterized by UV-absorbance-detected thermal melting experiment how a triplex structure stability may be affected by the residues adjacent to the triplex. Triplexes with varied strand compositions (DNA-DNA2, RNA-DNA2, and RNA-RNA2) were studied. We found that the non-base-triple-forming Watson-Crick base pair of the duplexes adjacent to the 5′ ends of the triplex-forming oligonucleotide (TFO) can strengthen the DNA-DNA2 and RNA-DNA2 triplex formation. A 2-aminopurine residue was attached to the 5′ and 3′ ends, respectively, to monitor triplex formation. The 2-aminopurine fluorescence intensity is enhanced upon binding to a duplex to form a triplex, suggesting that the 2-aminopurine base becomes less stacked upon triplex formation. 2-Aminopurine fluorescence titration was used to measure the KD values of the triplex forming reactions and the effects of pH, Mg2+ and spermine on triplex stability.